THE HISTORY OF AN EMERGING MULTILINGUAL PUBLIC LIBRARY SYSTEM AND THE ROLE OF MOBILE LIBRARIES IN POST COLONIAL SINGAPORE, 1956-1991 - Han, Lim Peng (Malaysian Journal of Library and Information Science, 2010)
This paper traces the historical background and development of public library services in postcolonial Singapore from 1956-1991, with special emphasis on multilingual public library system and the role of mobile libraries. After Sir Stamford Raffles founded Singapore in 1819 on behalf of the East India Company he planned to establish a college with a multilingual library. However, it began as an elementary school library (1823-1844) with English books, and evolved into a proprietary library (1844-1874), Government library (1874-1941), Japanese library (1942-1945) and Government library (1945-1958). In 1956 the library began to source books in the vernacular languages. In 1958 it became a National Library and public library. Two part-time branches and two mobile libraries known as the Library Extension were set up in 1960. By 1963, there were 7 per cent Malay books, 19 per cent Chinese books, 6 per cent Tamils books, and 68 per cent English books. The mobile library service points increased from 2 in 1964 to 12 in 1969. During the mid-1960s and up to 1970 the Library Extension Unit had about 20 per cent membership of the total public library system. Although Raffles wanted his proposed institution to have a multilingual library in 1823, it was not until 1970 that the library evolved into one when there was sufficient collection to make it into a multilingual public library system. After eight full-time branch libraries were gradually set up from 1970 to 1988, the mobile library services were gradually reduced and terminated in 1991.